Kanal İstanbul'un Hidrolik Modellemesi - Akman, Mehmet Akif (Fen Bilimleri Enstitüsü, 2016)
Türk Boğazlar Sistemini oluşturan iki boğazdan biri olan İstanbul Boğazı, Marmara Denizi ile Karadenizi birbirine bağlamakta, Çanakkale Boğazı ise Marmara Denizi ile birlikte ona bağlanan Karadeniz'i Ege Denizine, yani Akdenize bağlamaktadır. Başta Türkiye olmak üzere Karadenize kıyısı olan ülkeler için son derece kritik bir yol olan İstanbul Boğazından, güncel verilere göre bir yılda yaklaşık 55.000 gemi geçmekte olup, bunun üzerinde rakama ulaşıldığı zaman büyük aksaklıklar gözlemlenmektedir. Gemi trafiği arttıkça, Boğazdan geçecek deniz taşıtlarının uzun süre beklemeleri gerekmekte, uzun kuyruklar oluşabilmekedir. Bu durum hem İstanbul açıklarında yüksek deniz taşıtı yoğunluğu, hem kirlilik, hem de ekonomik kayıplara yol açmaktadır. Bu gibi sebeplerle, belirtilen uzun bekleme sürelerinin önlenmesi, ekonomik kayıpların önüne geçilmesi ve boğaz güvenliğinin arttırılması maksadıyla, yapılması planlanan Kanal İstanbul projesi önemli bir yatırım olarak öne çıkmaktadır. Bu doğrultuda, yürütülmekte olan Kanal İstanbul Projesi Güzergâh alternatifleri araştırması çalışmaları sonucunda, başta teknik ve ekonomik yapılabilirlik ile navigasyon güvenliği olmak üzere çok sayıda parametrenin dikkate alınmasıyla Küçükçekmece Sazlıbosna – Durusu (Terkos'un Doğusu) Koridoru uygun güzergah olarak ilgili kurumlarca daha önce belirlenmiştir. Bu çalışmada, Kanal İstanbul için belirlenen güzergâhta oluşan hidrolik etkiler incelenmiş olup, farklı derinlik ve farklı zemin kaplamaları için model kurularak çalışmalar yapılmıştır. Bu çalışmaya ek olarak, güzergah üzerinde bulunan Terkos Gölü, yine güzergah üsündeki akiferlerle iletişim, sediment taşınımı, çevresel etkiler vb. gibi hususlar içinde ayrıca çalışma yapılması gerekmektedir. Bu çalışmadaki amaç, Kanal İstanbul'un yapımı durumunda kanal içinde oluşacak hidrolik etkileri gözlemleyebilmektir. Bu kapsamda Delft3D yazılımı ile hidrolik modelleme yapılmış, muhtemel değişiklikler ve oluşacak durum incelenmiştir. Özellikle TBS'de gözlenen tabakalı akımın oluşup oluşmadığı, kaç metre derinlikten sonra oluştuğu ile ilgili gözlemler yapılmıştır.

The Bosphorus is one of the two Bosporus of the Turkish Strait System which connects Marmara Sea and The Black Sea. The other Bosporus of the Turkish Strait System is The Dardanelles which connects The Marmara Sea and The Aegean Sea that connects The Mediterranean Sea. In particular, these two Bosporus are extremely critical way for countries bordering the Black Sea including Turkey. According to latest information, about 55,000 ships for a year pass through the Turkish Strait System. When the number reached on these figures, great difficulties is experiencing. By the increase of the ship traffic every year, it is obligatory to wait longer to pass through the Strait of Bosporus. So there should be long queues. In this case, the high density of sea vehicles in the open sea of İstanbul, can be dangerous for sea nature and also causes both pollution and economic losses. For such the reasons, preventing of long waiting times, increasing the safety of Bosporus and preventing economic losses, Canal İstanbul is being a very important project for both Istanbul and the Bosporus. In this context, the route of the Canal Istanbul Project is being executed as a result of researches, especially the technical and economic feasibility with navigation safety, including many by taking into account the parameters. The route which has been identified as the most suitable route is the Küçükçekmece Sazlıbosna - Durusu (East of Terkos) corridor. This study examines the hydraulic impact of Canal Istanbul on the designated routes and the work was done by establishing different models for different depths and different bed coverings. Different studies have been done by establishing different models for different depths and bed coverings. At first, by taking the depth as a constant value and different hydraulic bed covering were examined and the effects of the roughness to the canal was studied. After that, roughness is taken as a constant value and the effect of the change of the depth was studied separately. In this context, hydraulic modelling is done with Delft3D software. 9 different model is examined and the results are studied. Every model studied separately by the terms of temperature, salinity, velocity distribution and the estimated discharge values through the canal cross-section. As known, Water circulation along Istanbul Strait, includes very complicated and comprehensive processes, because of differences between North and South part of Istanbul Strait. North part of Istanbul Strait is an exit to Black Sea. Black Sea is an interior sea, which has lower salinity according to Marmara Sea and higher water level. Especially, Danube River's freshwater discharge towards Black Sea, leads to low salinity (approximately 18 ppt) and high water levels. Because of brackish water discharge from Mediterranean Sea, Marmara Sea is saltier than Black Sea. (approximately 34-35 ppt where the canal connects with Marmara Sea). Before starting modelling steps, some data sets obtained for model reliability. Hydrographic Data, Water level Data both Marmara Sea and Black Sea and some meteorological data is obtained from related Administrations. Hydrographic data is obtained by General Directorate of Istanbul Water and Sewerage Administration (ISKI). Hydrographic data, is a time series(monthly) which includes temperature and salinity parameters with depth-changing. This data is observed by monthly periods. In a year, there are 12 different hydrographic observations. Hourly observations of Water Level data are observed by Turkish Naval Forces. Water level observations are executed at two different stations, which are north and south part of the strait. Meteorological data are obtained by ECMWF and AKOM. From ECMWF, sea level air pressure observations are obtained. From AKOM, Temperature, Relative Humidity and Cloudiness data are delivered. After completing data collection, 3 dimensional modelling process has just started. With the hydrodynamic model, 9 different models for different depths and different roughness values was modelled. Firstly, horizontal mesh created and after creation of mesh vertical layers is modelled for every 5-meter depth separately. In these studies, the minimum number for vertical layers are 4 and the maximum number of vertical layer is 8. Initial conditions are water level, salinity and the temperature. In that case both water level and discharge speeds are estimated as 0, salinity is taken as 19 ppt and temperature is taken 0 oC. Boundary conditions are taken same as initial conditions like water level, temperature and salinity. In the 4th part of this thesis, output records are given. Every records investigated in this part. For every results of all 9 model, temperature, salinity, water speeds at the canal and the discharge values studied separately. After evaluation of all models, the most appropriate canal section is chosen as 30-meter depth and the slope coverage with concrete and the canal ground is left as excavated. The results are valid for chosen canal corridor which connects The Marmara Sea and The Black Sea. This study is done for hydraulic solutions and contains only hydraulic results on the canal and does not contain any recommendation for constructing or not. If construction will be started, the effects of the construction of canal to the environment must be study very carefully.
Hydraulic Modelling Of Canal Istanbul
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Kanal İstanbul Su Yolu; Canal Istanbul Water Way